Ecofeminism: Resistance to Ecological and Female Oppression - Shrestha, Ravi Kumar (Patan Pragya, 2024)
Eco-feminism is a movement and an ideology against the oppression of nature and females. It shows a link between nature and females that are exploited and oppressed by males in the world. It discovers that the position of the nature and women is similar and both are treated as submissive and subservient subjects. It is related to masculine domination in the society. Historically, it appeared as a great political movement in the late 1970s and early 1980s in the west. It was Francoise d'Eaubonne who first developed the term ecological feminism in 1972 discussing that the destruction of the planet is due to the profit motive of the males. Since both nature and female are violated and suppressed by patriarchal or male superiority ideology, ecofeminism as a movement appears powerful to resist the oppression of both nature and female. The principal objective of the research is to explore how ecofeminism acts a defense for preserving the rights of both women and nature. Hence, this paper explores how ecofeminism as a movement and ideology defends the rights of women and nature that should be preserved for the preservation of ecology and human rights on the earth. According to Greta Gaard, eco-feminism provides a theoretical bridge for women working in the related movements of environmentalism, animal liberation and feminism. Linking both rights of nature and women, it includes the voices of trees, animals and women and fights for the liberation of them resisting any force against the exploitation and oppression of both nature and women. Therefore, becoming aware of Gaard’s views on ecofemenism, her theory of ecofeminism can be applied as a major theoretical lens for the broad theoretical framework. The major finding of the paper is that ecofeminism as a theory or movement or ideology is needed to fight to resist the oppression of women and nature globally to maintain ecology rights of women.